Study on mechanical properties of high strength sorbite stainless steel S600E under monotonic and cyclic loadings. (December 2021) - Wang, Jiachang; Shu, Ganping; Xu, Xiu; Dong, Shutong; Zheng, Baofeng
Abstract: A new kind of high strength sorbite stainless steel named S600E was developed recently, which has the 65% corrosion resistance, but three times higher yield strength than commonly used austenitic stainless steel S30408. In addition, the price of S600E is only 70% of S30408 owning to the low nickel content of 1.5–2.5%. Fundamental investigations on the mechanical behaviours of S600E were presented in this study. Two monotonic and seventeen cyclic material tests were conducted subjected to different strain-controlled loading protocols including the constant strain amplitude ranging from 0.25% to 2.5%, as well as the varied strain amplitudes. Monotonic test results show that S600E presents the typical feature of rounded nonlinear strain hardening, but the 0.2% proof stress is extremely high, up to 750 MPa, and the elongation after fracture is over 20%. In the cyclic tests, little cyclic hardening was occurred in the initial few cycles, while cyclic softening tended to appear at the remaining cycles. Based on the test results, the isotropic component in the constitute model was neglected, key material parameters for the nonlinear kinematic hardening model with two pairs of backstresses were obtained and validated using the numerical analysis in ABAQUS. At last, the cyclic material properties were compared with commonly used stainless steel to reveal the advantages of S600E. The results of this study could be used in finite element modeling of members, joints and structures of S600E.